Alkaline phosphatase interference in immuno-enzymatic assays. - oğuz, OSMAN; Serin, Huriye; Hocaoğlu Emre, Fatma (Journal of Medical Biochemistry, 2021)
Background: Alkaline phosphatase (ALP) enzymes are widely used as signal amplifiers in immunoenzymatic methods. Conditions that cause ALP elevations, such as bone or liver diseases can cause interference in immunoenzymatic methods. Objective: We aimed to examine ALP’s effect on immunoenzymatic assay by adding isolated pure ALP to the prepared serum pool. Material and Methods: We prepared a serum pool and divided into 4 groups. By adding isolated pure ALP at different concentrations to each group, we obtained sample groups containing ALP enzyme at concentrations of 85 U/L, 340 U/L, 870 U/L and 1570 U/L. In each group, 20-repetition of βhCG, Ferritin, FT4, TSH, Troponin I and Vit B12 tests were performed. Coefficient of variation, bias, and total error were calculated. All groups were compared by using Friedman test for paired samples. Result: After ALP addition, the calculated total error values of FT4, βhCG and troponin I tests were found to be above the acceptable error limits. There were statistically significant differences in βhCG ,FT4, troponin I and Vit B12 tests when compared to the baseline ALP level (P<0,0125). Conclusion: Isolated ALP elevations can be a source of interference for immunoenzymatic methods. Keywords Alkaline phosphatase, ALP, bias, immunoenzymatic, total error